Quantum key distribution for 5G networks: a review, state of art and future directions - Adnan, Mohd Hirzi; Ahmad Zukarnain, Zuriati; Harun, Nur Ziadah (MDPI, 2022)
In recent years, 5G networks and services become progressively popular among telecommunication providers. Simultaneously, the growth in the usage and deployment of smartphone platforms and mobile applications have been seen as phenomenal. Therefore, this paper discusses the current state of the art of 5G technology in the merger of unconditional security requirements referred to as Quantum Cryptography. The various domain of Quantum Cryptography is illustrated including the protocols available, their functionality and previous implementation in real networks. This paper further identifies research gaps covering critical aspects of how Quantum Cryptography can be realized and effectively utilized in 5G networks. These include improving the current technique in Quantum Cryptography through efficient key distribution and message sharing between users in 5G networks.